2018
DOI: 10.1002/smll.201801233
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable COF‐Supported Co/Co(OH)2 Nanoparticles Heterogeneous Catalyst for Reduction of Nitrile/Nitro Compounds under Mild Conditions

Abstract: Ordered nanoporosity in covalent organic framework (COF) offers excellent opportunity for property development. Loading nanoparticles (nPs) onto them is one approach to introducing tailor-made properties into a COF. Here, a COF-Co/Co(OH) composite containing about 16 wt% of <6 nm sized Co/Co(OH) nPs is prepared on a N-rich COF support that catalyzes the release of theoretical equivalence of H from readily available, safe, and cheap NaBH . Furthermore, the released H is utilized for the hydrogenation of nitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 46 publications
5
66
0
2
Order By: Relevance
“…These results suggested that nickel nanoparticles were the active sites for the hydrogenation of nitriles. Generally, metallic nanoparticles have the ability to activate molecular hydrogen in chemical reduction reactions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that nickel nanoparticles were the active sites for the hydrogenation of nitriles. Generally, metallic nanoparticles have the ability to activate molecular hydrogen in chemical reduction reactions …”
Section: Resultsmentioning
confidence: 99%
“…However, the hydrogenation of nitriles by homogeneous catalysts has distinct drawbacks in terms of the difficulty of recycling and reuse of the homogeneous catalysts as well as the contamination of the target products with trace amounts of metal from the homogeneous catalysts, which is detrimental to pharmaceuticals. To overcome the issues of homogeneous catalytic systems, a considerable effort has been devoted to the design of new heterogeneous catalytic systems for the hydrogenation of nitriles, which have been mainly based on precious metals. Undoubtedly, the use of expensive noble‐metal catalysts would result in high production costs in practical applications.…”
Section: Introductionmentioning
confidence: 93%
“…However, the TON is not remarkably high because only certain facets of the Ag nPs are exposed to the surface for catalytic activity. Also, the atoms in the core of the cluster are not accessible to the reactants …”
Section: Resultsmentioning
confidence: 99%
“…[212] Similarly,C o@CTF with Co/ Co(OH) 2 nanoparticles catalyzes the reduction of arylnitrile and arylnitro compounds to arylamines in 87 %y ield. [213] Hydrazone-linked Ru@COF-ASB (Figure 49 g) promotes the solvent-free one-pot tandem oxidation-condensation between benzylic alcohols and arylamines in air to afford aw ide range of imines in yields of 70-91 %. [214] b-Ketoenamine-linked PtNPs@COF (Figure 49 h; NPs = nanoparticles) transforms 4-nitrophenol into 4-aminophenol, with 100 %c onversion within 8min, [215] which is faster than AuNPs-COF (13 min).…”
Section: Angewandte Chemiementioning
confidence: 99%